A case of inflammatory-related urethral tumor in a child - Hongjia He; Meng Gui; Kaisheng Li (Urology Case Reports)
A rare pediatric urethral mass presented with penile root pain, urinary stream narrowing, and acute urinary retention without trauma or infection history. Examination revealed abdominal distension and a tender penile base mass. Laboratory and imaging findings indicated inflammation and a cystic lesion. After catheterization and antibiotics, symptoms resolved completely, and no recurrence was noted. Although cystoscopic resection is commonly advised, this case highlights that conservative management may be effective in selected patients, potentially sparing children from invasive procedures.